Barriers in the implementation of isoniazid preventive therapy for people living with HIV in Northern Ethiopia: a mixed quantitative and qualitative study - Gebrehiwot Teklay; Tsigemariam Teklu; Befikadu Legesse; Kiros Tedla; Eveline Klinkenberg (BMC, 2016)
Abstract Background Isoniazid preventive therapy is a key public health intervention for the prevention of tuberculosis disease among people living with HIV. Despite the confirmed efficacy of isoniazid preventive therapy and global recommendations existing for decades, its implementation remains limited. In resource constrained settings, few have investigated why isoniazid preventive therapy is not implemented on full scale. This study was designed to investigate the level of isoniazid preventive therapy implementation and reasons for suboptimal implementation in Tigray region of Ethiopia. Methods A review of patient records combined with a qualitative study using in-depth interviews and focus group discussions was conducted in 11 hospitals providing isoniazid preventive therapy in the Tigray Region. The study participants were health providers working in the HIV clinics of the 11 hospitals in the province. Health providers were interviewed about their experience of providing isoniazid preventive therapy and challenges faced during its implementation. All conversations were audio-recorded. Record review of 16,443 HIV patients registered for care in these hospitals between September 2011 and April 2014 was done to determine isoniazid preventive therapy utilization. Data were collected from April to August 2014. Results Fifty health providers participated in the study. Overall isoniazid preventive therapy coverage of the region was estimated to be 20 %. Isoniazid stock out, fear of creating isoniazid resistance, problems in patient acceptance, and lack of commitment of health managers to scale up the program were indicated by health providers as the main barriers hindering implementation of isoniazid preventive therapy. Conclusion Implementation of isoniazid preventive therapy in Tigray region of Ethiopia had low coverage. Frequent interruption of isoniazid supplies raises the concern of interrupted therapy resulting in creation of isoniazid resistance. Health managers, drug suppliers and partners working in HIV and tuberculosis programs should be committed to ensure an uninterrupted supply of isoniazid and full scale implementation of isoniazid preventive therapy to eligible people living with HIV.